Productivity growth in Malaysian manufacturing sector: A two stage analyses of the malmquist luenberger productivity index - Doraisamy, S.M.; Ramli, N.A. (2014)
Productivity growth must reflect the realities of production activities. In the manufacturing sector, emissions from fossil fuel combustion, which are acknowledged as being undesirable outputs, should be taken into account in productivity change measurement. The main purpose of this study is to calculate productivity change using the Malmquist Luenberger Productivity Index (MLPI) on the 15 states in Malaysia. Two stage analyses with a three year ‘window’ of data is employed to overcome the infeasibility problem that may occur in the MLPI calculated by Directional distance function (DDF). It was found that the main source of the productivity deterioration when taking carbon dioxide (CO2) emissions into account is eco-efficiency change.